Study of Traffic Noise Pollution at Penang Sentral Area, Butterworth, Penang - Mohamad Fauzi, Noor Farahin; Daud, Zawawi (Recent Trends in Civil Engineering and Built Environment, 2024)
Noise pollution has become a major environment issue that happen at the urban area in the city. The noise pollution can affect the mental and physical health of the people nearby the resources of the sound. The lack of sleep, poor performance during working or studying and hearing impairment is one of the impacts because of constant noise pollution. The objectives of this research are to measure the traffic noise level at three difference area which are SMK Convent Butterworth, KTM Butterworth, and Surau Al- Hidayah Balai Pukat. The objective is to determine the traffic noise index and equvalent continuous noise pollution at three differences area which are SMK Convent Butterworth, KTM Butterworth, and Surau Al-Hidayah Balai Pukat and lastly to identify the awareness about the traffic noise pollution around the Penang Sentral community. The research area is Penang Sentral, Butterworth, Pulau Pinang. The hand-held sound level meter has been used to collect the data. The research will be conduct during peak hour for 5 days at three different stations around Penang Sentral area. The aim of this study is able to reduce the noise pollution and improve the health of the student and residents. The result from this study is there are noise pollution around the Penang Sentral area. The LAeq has exceed 70 dBa at the Surau Al Hidayah and KTM Butterworth. The TNI at the 3 location also has exceed 74 dBa. The people around the area also aware about the noise pollution in Penang Sentral area and they agree that noise pollution can cause health problem. The authorities play a big roles to overcome this problem. They have to plan the city planning before approve the building to be constructed. At the Penang Sentral area indeed has a noise pollution around the area.